Remarkable genetic divergence of Gymnodiptychus dybowskii between south and north of Tianshan Mountain in northwest China. (February 2015) - Meng, Wei; Yang, Tian-yan; Guo, Yan; Hai, Sa; Ma, Yan-wu; Ma, Xu-fa; Cai, Lin-gang
Abstract: Gymnodiptychus dybowskii is endemic to Xinjiang, China and has been locally listed as protected animals. To investigate its genetic diversity and structure, specimens were collected from six localities in Yili River system and Kaidu River. Fragments of 1092bp Cyt b gene were sequenced for 116 individuals. A total of 21 haplotypes were found in all samples, and no haplotype was shared between Yili River system and Kaidu River population. Sequence comparisons revealed 123 variable sites, with eight singleton sites and 115 parsimony informative sites. For all the populations examined, the haplotype diversity ( h ) was 0.8298 ± 0.0226, nucleotide diversity ( π ) was 0.2521 ± 0.1202, and average number of pairwise nucleotide differences ( k ) was 275.3369 ± 118.5660. AMOVA analysis showed that the differences were significant for total populations except for Yili River system populations. The pairwise Fst values revealed same conclusion with AMOVA analysis: Kaidu River population was divergent from Yili River system populations. The genetic distance between two groups was 0.108 and the divergence time was estimated at 5.4–6.6 Ma, the uplift of Tianshan Mountain might have separated them and resulted in the genetic differentiation. The neutrality test and mismatch analysis indicated that both two groups of G. dybowskii had went through population expansion, the expansion time of Yili River system and Kaidu River population was estimated at 0.5859–0.7146 Ma and 0.5151–0.6282 Ma, respectively. The climate changes of Qinghai-Tibetan Plateau might have influenced the demographic history of G. dybowskii . Highlights: Genetic structure of Gymnodiptychus dybowskii from China was investigated. Remarkable genetic divergence was detected between two river systems. Uplift of Tianshan Mountain might result in the genetic differentiation. Climate changes of Qinghai-Tibetan Plateau might influence its demographic history.